Force-mediated molecule release from double network hydrogels. Issue 68 (5th August 2021) - Jayathilaka, Pavithra Bhakthi; Molley, Thomas Gregory; Huang, Yuwan; Islam, Md Shariful; Buche, Michael Robert; Silberstein, Meredith Natania; Kruzic, Jamie Joseph; Kilian, Kristopher Alan
Abstract : Mechanochemical release of molecules through a retro Diels–Alder reaction is demonstrated within double network hydrogels. Abstract : The incorporation of mechanosensitive linkages into polymers has led to materials with dynamic force responsivity. Here we report oxanorbornadiene cross-linked double network hydrogels that release molecules through a force-mediated retro Diels–Alder reaction. The molecular design and tough double network of polyacrylamide and alginate promote significantly higher activation at substantially less force than pure polymer systems. Activation at physiologically relevant forces provides scope for instilling dynamic mechanochemical behavior in soft biological materials.